Exploring pathways to Hospital Care for Patients with Alzheimer's disease and related dementias in rural South Western Uganda - Nathan Kakongi; Godfrey Zari Rukundo; Bizu Gelaye; Edith K. Wakida; Celestino Obua; Elialilia S. Okello (BMC, 2020)
Abstract Background In order to analyze use of health services and identify sources of delays in accessing the right care for patients with Alzheimer's disease and related dementias (AD/ADRD), understanding of care seeking pathways is needed. The objectives of this study were: (i) to explore pathways to hospital care for patients with AD/ADRD and (ii) to describe challenges experienced by the patients and their families while seeking health care. Methods Using purposive sampling, 30-in-depth, semi-structured interviews were conducted among caregivers of older adults diagnosed with dementia from rural Southwestern, Uganda. Data was analyzed using ATLAS. Ti software. Results There was variability in pathways to care from individual to individual. There was one broader theme captured: points of care choice with four broader categories: hospitals, clinics, places of religious worship and traditional healers' shrines, each with its facilitating factors, outcomes and challenges encountered. Most of the respondents reported use of hospitals at first and second visit to the health care point but places of religious worship became more common from third to sixth health care encounter. Major improvements (58.1%) were observed on hospital use but little or no help with prayers, clinics and traditional healers. The challenges experienced with formal points of care focused on lack and cost of prescribed drugs, weakening effect of the drugs, lack of skills to manage the condition, and lack of improvement in quality of life. These challenges together with knowledge gap about the disease and belief in spiritual healing facilitated the shift from formal to informal health care pathways, more particularly the places of religious worship. Conclusions Our study findings indicate that caregivers/families of patients with dementia went to different places both formal and informal care settings while seeking health care. However, hospital point of care was more frequent at initial health care visits while places of worship took the lead at subsequent visits. Although no specific pathway reported, most of them begin with hospital (formal) and end with non-formal. We recommend that health systems carry out public awareness on dementia.